Repositioning The Legislative Power of The DPR in The Formation of Responsive Laws in Indonesia - Winasis Yulianto; Dyah Silvana Amalia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This research aims to analyze the shift in the legislative power of the House of Representatives (DPR) following the amendments to the 1945 Constitution and its implications for the formation of responsive laws. The research method employed is normative legal research with a statutory and conceptual approach. The findings indicate that although Article 20, Paragraph (1) of the 1945 Constitution has granted the DPR the power to form laws, in practice, the process remains heavily dependent on joint approval with the President. To realize responsive legislation, the DPR needs to optimize the National Legislation Program (Prolegnas) and expand public participation spaces to ensure that the legal products generated are not repressive but instead reflect the genuine will and needs of the community.